The great green notebook of Katie Roberts : who just turned 12 on Monday - Hest, Amy.; Lamut, Sonja (Cambridge, Mass. : Candlewick Press, 1998)
In a series of journal entries, letters, pictures, and drawings, Katie relates her feelings about her mother, baby brothers, new friends, school, boys, the Italian immigrant she tutors, and growing up.
Accelerated Reader AR
Keywords: Family life -- Fiction; Schools -- Fiction; Diaries -- Fiction